KUALITAS KAYU SUNGKAI (Peronema canescens) DAN SENGON (Paraserianthes falcataria) PADA HUTAN RAKYAT DI KABUPATEN TABALONG KALIMANTAN SELATAN (Wood Quality of Peronema canescencs and Paraserianthes falcataria in the Community Forest of Tabalong, South Kali: Wahyudi, M. Damiri, Christopheros, Pahawang - Admin JHT (HUTAN TROPIKA, 2018)
ABSTRACTCommunity forest has a big value to be developed in the scrubs and degraded land thatgone the round of land in Indonesia. Developing community forest is able to increase product ofdomestic wood, moreover, community forest also can improve social earnings. This research wasaimed to know the history of community forest using species of Peronema canescens andParaserianthes falcataria in Tabalong District, South Kalimantan Province and also to knowexpectation and constraint met. The result of this research indicates that density of plans are lowand mixed with other plant. The densities of sengon and sungkai area are 158 trees/ha and 132trees/ha, respectively. Stem quality of Peronema canescens and Paraserianthes falcataria isstill low. Empowerment and construction in order to develop the community forest are veryimportant to be done.Keywords : Community forest, Peronema canescens, Paraserianthes falcataria